What are the main differences between the practice of supervising large banks in the UK and in the euro area, and what are the main risks of regulatory divergence? - Rainer Haselmann; Tobias Tröger (Leibniz Institute for Financial Research SAFE, 2021)
This in-depth analysis provides evidence on differences in the practice of supervising large banks in the UK and in the euro area. It identifies the diverging institutional architecture (partially supranationalised vs. national oversight) as a pivotal determinant for a higher effectiveness of supervisory decision making in the UK. The ECB is likely to take a more stringent stance in prudential supervision than UK authorities. The setting of risk weights and the design of macroprudential stress test scenarios document this hypothesis. This document was provided by the Economic Governance Support Unit at the request of the ECON Committee.
Keywords: 330; Bank Supervision; Economic Governance; Banking Union; Brexit